Variation of Aedes aegypti Larvae Predation by Toxorhynchites violaceus Larvae (Diptera: Culicidae) According to Habitats Dimensions - Albeny, Daniel Simões; Rosa, Cassiano Sousa; Krüger, Rodrigo Ferreira; Ataíde, Lívia Maria Silva; Vilela, Evaldo Ferreira (BioAssay, 2012)
Non-biodegradable containers that accumulate water are commonly found in urban environment, and make ease the larval development of Aedes aegypti mosquito. Wich can make chemical control very difficult and less effective. Biological control is an alternative method, and the predators Non-biodegradable containers that accumulate water are commonly found in urban environment, and make ease the larval development of Aedes aegypti mosquito, which can make chemical control very difficult and less effective. Biological control is an alternative method, and the predators larvae of the genre Toxorhynchites (Diptera: Culicidae) are a model widely used. In this article we check the effect of habitat heterogeneity on Ae. aegypti larvae predation by larvae of Toxorhynchites violaceus. The predation model defines that the habitat heterogeneity has a significant effect on predation level. Larvae suffers a higher predation in containers with 1.8 centimeters in high of the water column than in containers with 4 and 13.4 centimeters high. In large containers, the predation of Ae. aegypti larvae by Tx. violaceus larvae may not be efficient. However, in containers that accumulate small water volume, as in the majority of the non-biodegradable containers, the model may be efficient. KEYWORDS – Toxorhynchites, containers, heterogeneity, Ae aegypti.